The monetary system : analysis and new approaches to regulation - Serval, Jean-François; Tranié, Jean-Pascal (Wiley finance series., 2015)
"The authors offer an analytic approach distinguishing those financial instruments that are freely transferable and those that can be classified as securitization and CDS as a result of their underlying legal structure from other financial instruments that can often be converted from one category to another. Their new aggregates M5 category encompass all instruments including cash from the Central Bank, in essence all receivables that in counterparty relationships are recorded as debts in some balance sheets, the M6 entry being the total of balance sheets from where the data has to be collected to compare them with revenues. By employing derivatives of M5 and M6 they cover all underlying collateral classes thus allowing a type of comprehensive economic modeling that no other authors have been able to propose. This text offers insights into the present situation of slow growth, rising debts and long term low inflation and puts forward some possible outcomes for the global economy. The authors point out the social role of monetary contracts not only because they are grounding exchanges as it has always been the since ever in the past but also because it's sampling is the tool for redistribution between actors including "sectors" through taxation and inflation and deflation and finally between generations"--